1998
DOI: 10.1016/s0014-5793(98)01107-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity inhibits the genetic expression of interleukin‐2 and its receptor in mitogen‐activated T lymphocytes

Abstract: Experiments conducted in space in the last two decades have shown that T lymphocyte activation in vitro is remarkably reduced in microgravity. The data indicate that a failure of the expression of the interleukin-2 receptor (measured as protein secreted in the supernatant) is responsible of the loss of activity. To test such hypothesis we have studied the genetic expression of interleukin-2 and of its receptor in concanavalin Aactivated lymphocytes with the RT-PCR technology. Microgravity conditions were simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 23 publications
12
90
1
Order By: Relevance
“…The expression of early genes regulated primarily by transcription factors NF-κB, CREB, ELK, AP-1, and STAT were impaired in microgravity, suggesting that microgravity either slows, impedes, or fully blocks key signaling pathways in early T cell activation (Boonyaratanakornkit et al, 2005). They showed that IL-2 was among the down-regulated genes, which correlates well with previous nonarray based reports (Cogoli et al, 1993;Pippia et al, 1996;Walther et al, 1998;HughesFulford et al, 2005). Interestingly, IL-2 was also significantly decreased (and IL-10 expression was increased) in a recent real time PCR based analysis of gene expression in T-cells of mice after being flown in space aboard STS-118 for 13 days (Gridley et al, 2009).…”
Section: Microarray Analysis Of Microgravity Exposed Cells Of the Immsupporting
confidence: 84%
See 1 more Smart Citation
“…The expression of early genes regulated primarily by transcription factors NF-κB, CREB, ELK, AP-1, and STAT were impaired in microgravity, suggesting that microgravity either slows, impedes, or fully blocks key signaling pathways in early T cell activation (Boonyaratanakornkit et al, 2005). They showed that IL-2 was among the down-regulated genes, which correlates well with previous nonarray based reports (Cogoli et al, 1993;Pippia et al, 1996;Walther et al, 1998;HughesFulford et al, 2005). Interestingly, IL-2 was also significantly decreased (and IL-10 expression was increased) in a recent real time PCR based analysis of gene expression in T-cells of mice after being flown in space aboard STS-118 for 13 days (Gridley et al, 2009).…”
Section: Microarray Analysis Of Microgravity Exposed Cells Of the Immsupporting
confidence: 84%
“…Because of the high-cost and low efficiency of space flown experiments, ground-based methods for simulating the microgravity environment have been developed. These simulated microgravity studies include head down bed rest for humans (LeBlanc et al, 2007), tail suspension for rodents (Sonnenfeld & Shearer 2002;, cell and microorganism cultures with high aspect ratio wall vessel bioreactors (RWV) (Schwarz et al, 1992;Tsao et al 1992;Hammond & Hammond 2001;Nickerson et al, 2003) and random positioning machines (RPM) (Hoson et al 1993;Walther et al, 1998;Pardo et al, 2005), denervation (Nikawa et al, 2004), and diamagnetic levitation (Dai et al, 2009;Hammer et al, 2009). Bed rest with the head tilted down at ~ 6˚ has been found to induce physiological alterations similar to those experienced in the space environment.…”
Section: An Overview Of Two Relevant Biotechnologies In Space Biosciementioning
confidence: 99%
“…The total sample package (20 Â 20 Â 10 cm 3 ) was mounted at the center of the two independent frames for which rotation is driven by two separate motors. The RPM was operated as a random walk three-dimensional clinostat (basic mode) with an angular velocity of rotation of 60 deg s À1 (Walther et al, 1998) for 10 days (maximum cultivation time allowance for that facility). Random rotation at 60 deg s À1 , 1-10 cm away from the center of rotation, yields gravity contours from 1.12 Â 10 À3 to 1.12 Â 10 À2 g as calculated by g 0 ¼ (o 2 R)/g 0 , where o ¼ 1.05 radian s À1 , R ¼ 0.01-0.10 m and g 0 ¼ 9.81 m s À2 (Hoson et al, 1997;Boonyaratanakornkit et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Simulated microgravity (microarray) studies of Jurkat cells revealed an inhibited induction of 91 genes compared with normal gravity controls (10), whereas 10 genes regulated by key signaling pathways were confirmed by RT-PCR to have altered induction. In addition, differences between flight and controls for genes encoding various proteins involved in metabolism, signal transduction, adhesion, transcription, apoptosis, and tumor suppression have also been identified (8,46,113).…”
Section: Immune System Cellsmentioning
confidence: 99%